The Rising Dragon and The Defending Eagle: Understanding the Geopolitical Rivalry between U.S. - China in South China Sea - Hardhana Danastri (Journal of International Relations on Energy Affairs, 2020)
This paper aims to understand the geopolitical rivalry between the long-standing great power U.S. and the world’s emerging economic power China, particularly their rivalry within contested South China Sea. This article conducted qualitative methods to produce in depth analysis towards the phenomenon. One question is at stake which is what both powers want in South China Sea. The answer raises an additional inquiry; what kind of significances that South China Sea promises for either U.S. or China? This article argues that U.S. and China both strive for control over the territory. To answer the latter question, this paper is using a geopolitical approach, emphasizing on the lines of communication and centers of resources that South China Sea offers. This paper also argues that China’s geopolitical objective is intended to strengthen their regional hegemony, ultimately global pre-eminence in the long-term. Meanwhile, U.S. seeks to re-assert their power in the region and to rebalance their rising power.